2012
DOI: 10.1021/ol300670n
|View full text |Cite
|
Sign up to set email alerts
|

Simple Synthesis of β-Trifluoromethylstyrenes Using (E)-Trimethyl-(3,3,3-trifluoroprop-1-enyl)silane

Abstract: (E)-trimethyl-(3,3,3-trifluoroprop-1-enyl)silane (1) was synthesized as a reagent for use in Hiyama cross-coupling reactions for the production of β-trifluoromethylstyrene derivatives. Cross-coupling of 1 with electronically diverse aryl iodides was achieved by treatment with CsF in the presence of catalytic amounts of palladium to afford the desired products in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 36 publications
(15 reference statements)
2
14
0
2
Order By: Relevance
“…Recently, Prakash et al [30] reported the synthesis of β-trifluoromethylstyrenes through a Heck coupling reaction of aryl iodides with 1-iodo-3,3,3-trifluoropropane, allowing a direct introduction of 3,3,3-trifluoropropenyl groups to aromatic rings. Approximately at the same time, our research group demonstrated that ( E )-trimethyl(3,3,3-trifluoroprop-1-en-1-yl)silane ( 1 ) effectively participated in a Hiyama cross-coupling reaction with aryl iodide to construct β-trifluoromethylstyrenes in good to excellent yield [3132]. In the course of this study, we found that the reaction of 1 with benzaldehyde in the presence of fluoride anions afforded an allyl alcohol, which spontaneously isomerized to phenyl 3,3,3-trifluoropropyl ketone ( 3a ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Prakash et al [30] reported the synthesis of β-trifluoromethylstyrenes through a Heck coupling reaction of aryl iodides with 1-iodo-3,3,3-trifluoropropane, allowing a direct introduction of 3,3,3-trifluoropropenyl groups to aromatic rings. Approximately at the same time, our research group demonstrated that ( E )-trimethyl(3,3,3-trifluoroprop-1-en-1-yl)silane ( 1 ) effectively participated in a Hiyama cross-coupling reaction with aryl iodide to construct β-trifluoromethylstyrenes in good to excellent yield [3132]. In the course of this study, we found that the reaction of 1 with benzaldehyde in the presence of fluoride anions afforded an allyl alcohol, which spontaneously isomerized to phenyl 3,3,3-trifluoropropyl ketone ( 3a ).…”
Section: Introductionmentioning
confidence: 99%
“…However, synthetic approaches to (trifluoromethyl)vinyl derivatives are relatively under-explored. Among the various methods, metal-mediated approaches to vinyl trifluoromethylation include: (a) Pdcatalyzed reactions of vinyl sulfonates with TMS- or TES-CF 3 , 4 (b) Cu-catalyzed reactions of vinyl bromides with TMS-CF 3 , 5 , (c) Fe- and Cu-catalyzed reactions of vinyltrifluoroborates and vinylboronic acids with Togni's reagent, 6,7 (d) Cu-catalyzed reaction of vinyl boronic acid with Umemoto's reagent, 8 (e) Cu-catalyzed decarboxylative trifluoromethylation with Togni's reagent, 9 (f) Cu- and Fe-catalyzed decarboxylative trifluoromethylation with Langlois reagent, 10,11 (g) Heck-like reaction on in situ formed 3,3,3-trifluoropropene, 12 (h) Hiyama reaction of aryl iodides with ( E )-trimethyl-(3,3,3-trifluoroprop-1-enyl)silane, 13 (i) redox-chemical methods involving Ir 14 and Ru 15,16 catalysts. Wittig- and Horner-type reactions have also been evaluated as approaches to vinyl trifluoromethylated compounds.…”
mentioning
confidence: 99%
“…After screening various reaction parameters, we were pleased to observe 78% NMR yield of the desired pyrrolidone product 3 a, using 1.0 equiv. [22] It is noteworthy that other Lewis acid-catalytic systems such as CuCl 2 , ZnCl 2 , InCl 3 , and FeCl 3 were found to be totally ineffective under identical reaction conditions (entries [2][3][4][5]. The structure of 3 a was unequivocally confirmed by single crystal X-ray analysis (Figure 2).…”
Section: Resultsmentioning
confidence: 94%
“…Given the unique physicochemical properties engendered by the trifluoromethyl (CF 3 ) group, considerable efforts have been directed towards new methodologies for the selective introduction of CF 3 groups into bioactive molecules. Conventional approaches for the synthesis of C vinyl ÀCF 3 compounds mainly rely on the coupling of aryl halides with highly volatile reagents, such as 1iodo-3,3,3-trifluoropropane, [4] (E)-trimethyl-(3,3,3-tri-fluoroprop-1-enyl)silane [5] and 2-(trifluoromethyl) acrylic acid, [6] and the direct trifluoromethylation reaction with unsaturated alkenes, [7] vinyl sulfonates, [8] vinylboron derivatives, [9] vinyl halides, [3b, 10] a,b-unsaturated carboxylic acids, [11] and other methods. [3] Therefore, development of efficient methods for the synthesis of these compounds is in great demand.…”
Section: Introductionmentioning
confidence: 99%